Jaringan Ilmu Nusantara – Timur Tengah, dan Peran Pesantren dalam Jaringan Tersebut - Adin, Ahmad Muchlis; Anshori, Muhammad Isa (Lembaga Yasin AlSys, 2024)
The development of Islamic Religion in the Nusantara cannot be separated from a tortuous process. Among the factors that triggered the development of the Islamic religion in the Nusantara was the connection and good relations that existed between the Javanese and Scholars who came from Middle East. They worked together to achieve their goal, namely to preach the religion of Allah on earth, thus the network among scholars are connected. Among the facilities used is building educational facilities in the form of madrasas and Islamic boarding schools, where these Islamic boarding schools will become the forerunners of Islamic education for the next generation who will continue this banner of da'wah.